āl-I’jāz al-Bayāni fii Sūrah āl-Insyirāh īnda Āisyah Binti āl-Syāthi’ waa Ālāqatuha bii Īlmi āl-Nafs lii āl-Murāhiq (Linguistic Studies) - Agus Budiman; Nailul Istibsyaroh; Ahmad Saifulloh; Nur Rochmatul Kamilah (Mantiqu Tayr: Journal of Arabic Language, 2024)
This research focuses on analyzing the beauty of the language in Surah āl-Insyirāh, which contains strong messages about consolation and strengthening in the face of difficulties. This research also examines the importance of these messages in the context of adolescent psychology, a critical period in the emotional and mental development of individuals. This research aims to reveal The graphic miracle, according to Āisyah Binti āl-Syāthi’, in Surah āl-Insyirāh, can be a guide for teenagers in facing the problems of their world, which is full of worries and anxieties. This research uses a qualitative research approach by collecting some data and then analyzing it until the research ultimately obtains important results with the presence of different aspects of the declarative miracle in Surah āl-Insyirāh. It has been found that Surat āl-Insyirāh has a profound linguistic beauty that can provide comfort and reinforcement. The message about there being ease after hardship, the importance of patience, and continuing to strive is very relevant to the challenges teens face. Āisyah Binti āl-Syāthi’s interpretation enriches the understanding of how these messages can be applied in the daily lives of teenagers, helping them develop emotional and mental resilience. Thus, this study shows that the graphic miracle of Surah āl-Insyirāh is not only amazing in terms of language but also has a positive impact on the mental health of teenagers. This research provides an explanation as well as an important contribution in literary and linguistic analysis to reveal the uniqueness of language style (i'jaz bayani) contained in Surah āl-Insyirāhwhich has a high beauty of language and a deep rhetorical structure. It is recommended that further research be conducted to expand the analysis to include other letters in the Qur’an and evaluate the effectiveness of applying these values in a broader and more diverse context.